O pensamento estocástico nos livros didáticos do ensino fundamental - Friolani, Luis Cesar (2007)
Our research had as its aims to verify the organisation of Middle-school mathematics textbooks (Grades 5 to 8) in relation to the topic Data Handling, analyse whether this organisation favours the construction of stochastic thinking and to examine whether the textbooks follow the orientation proposed in the PCN (National Curriculum Parameters). Given that the textbook tends to be the principal pedagogic support used by teachers (Lajolo, 1996 and Dante, 1996), we analyse three textbook collections using as our basis the idea of praxeological organisation (Chevallard, 1995), which involves identifying the tasks, the techniques and the theoretical-technological discourse. We also analyse the levels of statistical literacy, which, according to Shamos (1995), can be classified as cultural, functional e scientific. The results of the research indicate little exploration on the part of the authors in relations to the topic of Data Handling